2000
DOI: 10.1002/1096-987x(200010)21:13<1192::aid-jcc8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding interactions in the active site of a low molecular weight protein-tyrosine phosphatase

Abstract: Molecular dynamics simulation of the Michaelis complex, phospho-enzyme intermediate, and the wild-type and C12S mutant have been carried out to examine hydrogen-bonding interactions in the active site of the bovine low molecular weight protein-tyrosine phosphatase (BPTP). It was found that the S γ atom of the nucleophilic residue Cys-12 is ideally located at a position opposite from the phenylphosphate dianion for an inline nucleophilic substitution reaction. In addition, electrostatic and hydrogen-bonding int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Although the C-O and O-P bond lengths in the C124S mutant are shorter than the corresponding C-S and S-P bond lengths in the WT VHR, dephosphorylation would occur if Ser 124 were ionized. Hence, the phosphate group has enough mobility in the P-loop to be attacked by an ionized Ser 124 nucleophile, even if O γ is not optimally located [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the C-O and O-P bond lengths in the C124S mutant are shorter than the corresponding C-S and S-P bond lengths in the WT VHR, dephosphorylation would occur if Ser 124 were ionized. Hence, the phosphate group has enough mobility in the P-loop to be attacked by an ionized Ser 124 nucleophile, even if O γ is not optimally located [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…including structural alterations in the mutant [21][22][23], increased distance between nucleophile and substrate [22] and nucleophile protonation [23].…”
Section: Figure 1 First Reaction Step Of Ptp Catalysismentioning
confidence: 99%
“…In fact, this system provides an excellent example, illustrating the significance of correlating structural information from computation and X-ray crystallography with enzyme activity to understand catalysis. 193,194 The phosphate binding site of PTP is characterized by the signature loop with a sequence of CXX-NXXR(S/T), where X can be any residue. The nucleophile Cys12 is stabilized by hydrogen bonding interactions from the side chains of Asn15 and Ser19 and the amide group of Ser19, making it a thiolate ion by lowering its pK a 195 and positioning it in the center of the binding loop perfectly suited for the in-line nucleophilic attack (Figure 3).…”
Section: Transition-state Stabilization By Electrostatics Including Hmentioning
confidence: 99%
“…94,276 Correlation of catalysis with the change in average hydrogen bond distance in the enzyme has been analyzed for other systems, including the PTP phosphate hydrolysis reaction, and its origin in that case was attributed to the Walden inversion mechanism in the nucleophilic substitution reaction. 193,194 …”
Section: Enzyme and Substrate Conformational Dynamicsmentioning
confidence: 99%
“…It has been found that water prefers to form hydrogen bonds with oxygen atoms of peptide bonds in proteins [2,3]. Studies of the interactions between water and other molecules are important to understand more fully the role played by water in the biochemical behavior of the molecules [4][5][6].…”
Section: Introductionmentioning
confidence: 99%